TECHNOLOGICAL REGULATIONS FOR THE OPERATION OF THE WALNUT PROCESSING LINE - TSURKAN, OLEH; SPIRIN, ANATOLII; RUTKEVYCH, VOLODYMYR; DIDYK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A comprehensive analysis of a technological line for walnut processing is presented, and a technological regulation for its operation is developed with due consideration of the productivity of the main machines and the sequence of technological operations. The specific features of step-by-step raw material processing are disclosed, including reception, primary cleaning, active ventilation, washing, drying, calibration, mechanical cracking, and fractionation of walnut kernels. The influence of operating parameters of drying equipment, settings of cracking machines, and sorting systems on the quality of the final product and the overall energy efficiency of the process is substantiated. It is established that harmonization of machine throughput capacities is a key factor in ensuring continuity, stability, and reliability of the production process, as well as in preventing bottlenecks and excessive product losses at individual stages of processing.The proposed technological scheme makes it possible to minimize losses of whole kernels, increase the degree of product purity, and form high-quality commercial fractions that meet market and regulatory requirements. Particular attention is paid to the interaction between mechanical and thermal processes, which significantly affects kernel integrity, moisture content uniformity, and subsequent sorting accuracy.Promising directions for further modernization of the processing line are identified, including the implementation of digital monitoring and control systems, the use of energy-saving drying technologies, the improvement of cracking machine designs, and the integration of machine vision tools to enhance sorting precision and reduce the influence of the human factor.The obtained results can be effectively used for the optimization of industrial walnut processing lines and for improving their technological, energy, and economic efficiency under modern conditions of agro-industrial production.
Keywords: walnuts; technological line; drying equipment; walnut washing; active ventilation; calibration; splitting; kernel fractionation; throughput; energy efficiency; machine sorting